Knowledge Regarding Management of Diabetic Nephropathy Among Medical Officers (MO) at HUSM and Its Association With MO Profiles - Othman, Siti Kamariah (2011)
Background: Many studies had assessed the knowledge and practices among the physicians in the management of chronic kidney disease (CKD) but no specific study to assess the knowledge of medical officers regarding the management of diabetic nephropathy. Many patient with diabetic nephropathy are seen by medical officers level, who are less experienced than nephrologists to offer optimal care. It is not known whether knowledge regarding management of diabetic nephropathy among medical officers are adequate in care of diabetic nephropathy patient and whether characteristics of medical officer are associated with having adequate knowledge. Study Design: Cross-sectional study. Setting & Participants: Self administered Questionnaire to medical officers at two medical based department HUSM (n=102) with distribution of 51 Internal Medicine and 51 Family Medicine in April 2011. The questionnaire consist of four knowledge domains regarding management of diabetic nephropathy and had established validation. Predictor or Factor: MO characteristics, including age, sex, specialties, years since graduation, attended seminar, status (either service MO or Master MO) and year of master program. Outcomes & Measurements: Total performance score (maximum=35). Adequate level of knowledge determined by expert panels as score of ≥67%. Regression analysis of the association between MO profiles and overall MO knowledge of diabetic nephropathy. Results: Total 102 out of 108 (94%) eligible medical officers returned a completed survey. Overall, 49% of medical officers have adequate level of knowledge. All medical officers have managed diabetic nephropathy cases but even so, only 78% of them have attended seminars/ talks or workshops regarding diabetic nephropathy. Overall, no relationship between level of knowledge and MO specialties (Internal Medicine Vs Family Medicine department). There were also no significant relationship between level of knowledge and status of MO (service MO or master MO). There were significant relationship between level of knowledge and year of master (p=0.016) and year four masters MO had more than 7 fold greater odds of showing a adequate level of knowledge compared with MO who are not yet joining master (95% CI 1.44,36.20, p = 0.016). Limitations: The questionnaire type of study is limited to test all type of knowledge (such as recall, comprehension, application, analysis, synthesis and evaluation). Domain of patient management such as patient education were not included in this questionnaire. This study not addressed the attitude and practice of MO regarding management of diabetic nephropathy. Conclusion: We found that medical officers have significant gaps in their knowledge regarding management of diabetic nephropathy that might require further improvement for better future patient care. Master training may offer the best opportunity to improve the awareness and knowledge of diabetic nephropathy guidelines through more focused educational efforts.